Metalurgi serbuk magnesium untuk aplikasi scaffold tulang mampu terdegradasi - Sulis Dri Handono; Mafruddin Mafruddin; Tri Cahyo Wahyudi; Ardian Prayoga; Ilyas Shodikin; Arif Ardiyansah (TURBO [Tulisan Riset Berbasis Online], 2022)
Healing of bones damaged by accidents or other factors can be done by creating artificial bone structures or bone scaffolds that can initiate the growth of bone tissue and help support bones so they can function. The process of making bone scaffold can be done by powder metallurgy sintering process with magnesium material. The purpose of this study was to determine the effect of variations in sintering temperature and compaction pressure in the magnesium powder metallurgical sintering process on the compressive strength and microstructure applied to degradable bone scaffolds. The research method used is experimental method by making and testing powder metallurgical magnesium material. The powder metallurgy process was carried out with various sintering temperatures of 350°C, 400°C and 450°C and variations of compaction pressure, namely 231 MPa, 309 MPa and 386 MPa. The results showed that variations in sintering temperature and compaction pressure affected the compressive strength and microstructure. The sintering temperature of 450°C and compaction pressure of 386 MPa resulted in the lowest pore percentage rate of 15.14% and the highest compressive strength of 80.26 MPa.